Women in Islamic civilisation: their rights and contributions - Akhmetova, Elmira (2016)
This paper provides a general survey of the contributions made by women to science, knowledge and welfare in Islamic civilisation. The paper determines that early Muslims approached Islam and science in a holistic fashion, after adopting an epistemology which maintained a unity between science, technology and spiritual knowledge. The paper also suggests that, in the early age of Islam, women were given positions of trust and high responsibility in the spheres of leadership, education, and science. But, this empowerment of women in early Islam bears little relation to the conditions of women in modern-day Muslim societies, where women often suffer the most in conflict-ridden regions, whether from insecurity, domestic abuse, low education levels or poor medical care. The paper accordingly establishes a direct link between the absence of good governance and issues like gender inequality, the violation of the rights of women, and the current weakness of Muslims in science and technology. Without good governance, the status of women is unlikely to improve. If women’s rights to both a proper education and an occupation continue to be neglected, the equilibrium of Muslim society will be damaged, hindering its ability to produce innovative and passionate minds.